EFFECT OF DIALOGIC TEACHING ON VOCABULARY ACQUISITION AND PHONOLOGICAL AWARENESS AMONG FIRST GRADERS: AN EXPERIMENTAL STUDY (Contemporary Journal of Social Science Review, 2025)
Dialogic teaching is an effective approach for teachers and students to collaborate and expand upon each other's ideas. It can make the classroom more interactive and improve learning achievements. This research investigates how dialogic teaching can help Pakistani learners with different levels of English vocabulary (low, average, and high) and phonological awareness learn English better. There will be 60 first graders from a private school in Lahore who will be examined on their understanding of English vocabulary and phonological awareness. They will then be put into a selected group either a control or experimental group. A 3-month dialogic teaching program will be used in English classes every day. We will administer the t-test to look at the pre-test and post-test outcomes in a statistical way. Results from repeated tests ANOVA showed that students who were taught with dialogic teaching made much more progress in their expressive vocabulary knowledge on textbook items than those who were not taught with dialogic teaching, both in the low-level and high-level vocabulary groups. High-vocabulary group also made more progress in their phonological awareness. These results suggest that using conversation to instruct in English as a second language (ESL) helps pupils acquire the language.